Imaginer la ville de demain sans « reproduire les clichés » de genre - Elsa Koerner (EchoGéo)
Based on a sociological survey of departments in charge of designing and maintaining public spaces in three cities (Rennes, Strasbourg, Le Mans) seeking to integrate a gender perspective into urban production, the article questions the difficulties of imagining a "feminist" city. This paper stresses new leads to overcome the perceived neutrality of public space. Iconography and planning documents are tools for imagination of a city freed from the norms of the gendered social order. Therefore, urban planners should delve into a gender-sensitive analysis of reproductive work and its spatial configuration at the level of towns and agglomerations.